Resilience and psychological impact on Italian university students during COVID-19 pandemic. Distance learning and health. Issue 1 (2nd January 2022) - Quintiliani, Livia; Sisto, Antonella; Vicinanza, Flavia; Curcio, Giuseppe; Tambone, Vittoradolfo
ABSTRACT: COVID-19 epidemic has been spreading in the world causing strong psychological pressure for the global population. Quarantine has huge impact and can cause considerable psychological stress. The study aims to identify psychological stress, emotional changes, approach to studies, resilience skills related to the experience of the COVID-19 pandemic in a sample of university students. A sample of university students from the Campus Bio Medico University of Rome was studied. The participants responded to an online questionnaire packet that included socio-demographic information, COVID-19 impact on emotions and on university life, perceived stress (PSS-10) and resilience skills (RS-14). We received 955 responses. The respondents experienced an increase in perceived stress in 89.4% of cases (66% stress moderate and 23.4% high). Moreover, 54.4% of students reported decrease in attention span and difficulty in studying with consequent concern about the exam outcomes (55%). Resilience skills positively affect stressful events and in particular the COVID-19 impact on study and interpersonal relationships. The study shows a psychological impact of the Covid-19 emergency on college students. Stress significantly decreases learning and negatively affects psychological well-being of students. Resilience skills were a protective factor to overcome difficulties learning.